2022
DOI: 10.1038/s41746-022-00631-8
|View full text |Cite
|
Sign up to set email alerts
|

The performance of artificial intelligence-driven technologies in diagnosing mental disorders: an umbrella review

Abstract: Artificial intelligence (AI) has been successfully exploited in diagnosing many mental disorders. Numerous systematic reviews summarize the evidence on the accuracy of AI models in diagnosing different mental disorders. This umbrella review aims to synthesize results of previous systematic reviews on the performance of AI models in diagnosing mental disorders. To identify relevant systematic reviews, we searched 11 electronic databases, checked the reference list of the included reviews, and checked the review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 35 publications
1
19
0
Order By: Relevance
“…Potential explanations for this trend include the troubles associated with the high dimensionality and heterogeneity of genetic data, which necessitates the collection of large datasets and the usage of complex modelling techniques (Su et al, 2020). Additionally, it has been demonstrated that neuroimaging data produces more accurate classifiers than genetic data for diagnosing a variety of mental disorders (Abd-alrazaq et al, 2022;Su et al, 2020). Another potential explanation may be the maturity of the technology for deriving diagnoses based on genetic data relative to more recent advances, such as the utilization of behavioral data gathered through mobile devices, which may have caused a transition to more modern and convenient data acquisition approaches (Bennett et al, 2012;McGuffin et al, 2004;Su et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Potential explanations for this trend include the troubles associated with the high dimensionality and heterogeneity of genetic data, which necessitates the collection of large datasets and the usage of complex modelling techniques (Su et al, 2020). Additionally, it has been demonstrated that neuroimaging data produces more accurate classifiers than genetic data for diagnosing a variety of mental disorders (Abd-alrazaq et al, 2022;Su et al, 2020). Another potential explanation may be the maturity of the technology for deriving diagnoses based on genetic data relative to more recent advances, such as the utilization of behavioral data gathered through mobile devices, which may have caused a transition to more modern and convenient data acquisition approaches (Bennett et al, 2012;McGuffin et al, 2004;Su et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Yet, others observe that insufficient regulatory oversight could undermine that aim and harm vulnerable users ("bots could be programmed to infiltrate people's homes and lives en masse, befriending children and teens, influencing lonely seniors, or harassing confused individuals until they finally agree to services that they otherwise would not have chosen." [36][37] These debates underscore the need for crossdisciplinary input, including from those whose lives are affected by health-AI, to achieve equitable and non-discriminatory health AI. [38] National and international leaders increasingly advocate for interdisciplinary collaboration on AI regulation.…”
Section: The Importance Of Multidisciplinary Analysis On Key Issuesmentioning
confidence: 99%
“…While not a substitute for professional diagnosis, these tools can complement professional care by guiding individuals towards help, assisting practitioners in monitoring progress, and contributing valuable research data. AI-powered assessments and chatbots play a role in modern mental healthcare, but their integration should always be part of a comprehensive approach that includes professional evaluation and treatment (Abd-alrazaq et al, 2022(Abd-alrazaq et al, , 2023Omarov et al, 2023;Rathnayaka et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The rapid advancement of artificial intelligence (AI) has significantly impacted various facets of life, including the field of mental health (Abd‐alrazaq et al., 2022; Wilson et al., 2023). Technologies such as machine learning, natural language processing, and data analytics have become integral to digital mental health interventions, encompassing virtual therapy programs and even self‐diagnosis tools (Aboueid et al., 2019; Omarov et al., 2023; Rathnayaka et al., 2022; Su et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation